Virtual autopsy in SARS-CoV-2 breakthrough infection: a case report. (September 2022) - Filograna, Laura; Manenti, Guglielmo; Grassi, Simone; Zedda, Massimo; Cazzato, Francesca; Ryan, Colleen P.; Arena, Vincenzo; Pascali, Vincenzo L.; Colosimo, Cesare; Floris, Roberto; Oliva, Antonio
Highlights: SARS-CoV-2 breakthrough infections represent an important risk in vaccinated individuals. PMCT was concordant with histopathological features. PMCT represents a valid forensic tool in fatal cases of SARS-CoV-2 breakthrough infection. Abstract: It is well documented that COVID-19 vaccines are effective tools for limiting the pandemic. Unfortunately, as is true for all vaccines, SARS-CoV-2 infection in vaccinated individuals is still possible. We present an autopsy case of SARS-CoV-2 infection after vaccination ("breakthrough infection") in an elderly man with several comorbidities where post-mortem CT scan was performed. The death was histologically attributed to cardio-respiratory arrest due to ischemic heart failure related to superinfected COVID-19 pneumonia and pre-existing comorbidities. For the first time in the literature, PMCT imaging related to a fatal, autopsy case of breakthrough SARS-CoV-2 infection is reported. PMCT of the lungs, in accordance with histopathological results, showed few signs of COVID-19 pneumonia, large area of consolidation in the right lower lobe, interpreted as bronco-pneumonic focus, and hypostasis. These findings were well-correlated with the previously reported literature about both PMCT and clinical CT imaging of the lungs in non-vaccinated individuals with early COVID-19 pneumonia and about pulmonary clinical CT imaging in COVID-19 pneumonia in breakthrough SARS-COV-2 infections. Further studies are needed to cover the whole spectrum of PMCT lung imaging in fatal breakthrough SARS-CoV-2 infection, however, this case represent a first step for exploring this difficult challenge during SARS-CoV-2 pandemic using virtual autopsy.